IDENTIFICATION OF COMMUNITY DISEASE SYMPTOMS AROUND COMMUNITY GOLD MINES IN TERMS OF LENGTH OF STAY (>5 YEARS) IN THE WORKING AREA OF THE UPTD PUSKESMAS UJUNG PADANG RASIAN, SOUTH ACEH DISTRICT - Lensoni; Nurdin, Ambia; In Erosida (Transpublika Publisher, 2024)
Mercury (Hg) is a toxic material widely used in gold mining to refine the metal. The amalgamation process in gold processing has been shown to damage the environment and human health. Natural sources of mercury include volcanic gas and seawater evaporation. Mercury can enter the human body through skin contact, vapor inhalation, and consumption of contaminated fish. The study was conducted in June 2023 on 47 residents around gold mines in the Working Area of the UPTD Puskesmas Ujung Padang Rasian, South Aceh District, Aceh Province. The majority of respondents were male (97.10%) with an age range of 26-35 years (37.10%). The majority had S1 education (45.70%) and lived there for 17-25 years (22.80%). Common acute clinical symptoms included cough, nausea, vomiting, headache, diarrhea and abdominal pain. Chronic symptoms included somatosensory disturbances, headaches, muscle cramps, tremors, erythema and weight loss. The majority of respondents experienced symptoms such as cough (31 respondents), nausea (30 respondents), vomiting (25 respondents), headache (24 respondents), and diarrhea (18 respondents) due to mercury exposure.